BIOLOGIA COMPARADA DO BICHO-DA-SEDA ð˜—ð˜©ð˜ªð˜ð˜°ð˜´ð˜¢ð˜®ð˜ªð˜¢ ð˜³ð˜ªð˜¤ð˜ªð˜¯ð˜ª (DRURY) (LEP., Saturnidae) EM QUATRO GENÃ“TIPOS DE MAMONA - Negreiros, JosÃ©; Vendramin, JosÃ© Djair; Rodrigues, Maria Elisabeth V.; MendonÃ§a, Gerbson A. (REVISTA DE AGRICULTURA, 2020)
BIOLOGIA COMPARADA DO BICHO-DA-SEDA ð˜—ð˜©ð˜ªð˜ð˜°ð˜´ð˜¢ð˜®ð˜ªð˜¢ ð˜³ð˜ªð˜¤ð˜ªð˜¯ð˜ª (DRURY) (LEP., Saturnidae) EM QUATRO GENÃ“TIPOS DE MAMONA